A decade of global hourly aerosol observations from DSCOVR/EPIC using near-UV measurements - Torres, Omar; Jethva, Hiren; Ahn, Changwoo; Kayetha, Vinay (Frontiers in Remote Sensing, 2025)
The availability of air quality (AQ) and climate related satellite information from the Earth Polychromatic Imaging Camera (EPIC) on the Deep Space Climate Observatory (DSCOVR), at the Lagrange Point 1 (L1) orbital configuration significantly enhances the diurnal coverage over large areas of the Sunlit side of the globe. The simultaneous availability of L1 and Geostationary (GEO) observations, along with traditional low-Earth- orbit (LEO) satellite measurements, offers a unique opportunity for the integration of a truly global AQ-observing system. In this paper, we discuss the decadal aerosol record from near-UV observations made by the EPIC-DSCOVR sensor. The near-UV EPIC aerosol record (EPICAERUV) shows a large increase in the atmospheric carbonaceous aerosol load over the last decade. In addition to the well-known seasonally varying sources of carbonaceous aerosols produced by biomass burning, a new source of carbonaceous particulate associated primarily, but not exclusively, with wildfires in the northern hemisphere has emerged and has been consistently detected over the last 10 years by EPIC and other spaceborne sensors. Unlike biomass burning aerosols produced in tropical and sub-tropical regions and, generally, residing in the lower troposphere, carbonaceous aerosols from wildfires in mid and high-latitude regions often ascend to the middle and high troposphere and, in some instances, reach the lower stratosphere where their residence time is significantly longer than in the troposphere. Wildfires and severe dust storms over the last decade have been observed by EPIC on a global basis from Australia and Chile in the Southern Hemisphere to North America, Central Europe, Siberia, and China in the Northern Hemisphere. We show and document some of these prominent aerosol events using the EPICAERUV aerosol dataset.